REDUCTION OF AMMONIA EMISSIONS FROM THE COMPOSTING OF SLAUGHTERHOUSE SOLID WASTE USING ZEOLITE - Rhenny Ratnawati; Sugito Sugito (Universitas Trisakti, 2020)
The process of aerobic composting the slaughterhouse (SH) solid waste generate ammonia emissions. Aim: The objective of this research to study the ability of the adsorbent to use zeolite to reduce ammonia gas emissions during the composting process of SH solid waste. Methodology and Results: Reduction of ammonia emission is conducted during the aerobic composting process which is 50 days. The raw material composition of the composting process used was 100% rumen contents, 60% rumen contents: 40% straw, 50% rumen contents: 50% straw, and 40% rumen contents: 60% straw. Zeolite used in the form of granular size 100 mesh. The result of the research showed that the level of release of ammonia gas emissions during the composting process could be reduced by zeolite. Conclusion, significance, and impact study: The efficiency of reducing ammonia gas emissions using zeolite adsorbents in the composting process of SH solid waste ranges from 98.09 - 99.40% on average. Zeolite is an adsorbent that has high adsorption power because it has many pores and has a high ion exchange high capacity and serves as an absorbent cation that can cause environmental pollution.